Regulation of G protein-coupled receptors by palmitoylation and cholesterol - Goddard, A; Watts, A (BioMed Central, 2012)
Due to their membrane location, G protein-coupled receptors (GPCRs) are subject to regulation by soluble and integral membrane proteins as well as membrane components, including lipids and sterols. GPCRs also undergo a variety of post-translational modifications, including palmitoylation. A recent article by Zheng et al. in BMC Cell Biology demonstrates cooperative roles for receptor palmitoylation and cholesterol binding in GPCR dimerization and G protein coupling, underlining the complex regulation of these receptors.